Analysis of the Role of Non-Cash Digital Payments in Encouraging Financial Accountability in Micro, Small, and Medium Enterprises in West Bandar Jaya, Central Lampung - Dwi Auliana; Desi Wahyuni (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to analyze the level of adoption and the role of non-cash digital payments in promoting financial accountability among Micro, Small, and Medium Enterprises (MSMEs). The research method used is a qualitative approach with a descriptive design. Data were collected through questionnaires, interviews, and documentation involving MSME actors who have used digital payment platforms such as ShopeePay, DANA, and GoPay. The results show that the adoption level of digital payments is relatively high and has a positive impact on financial management, particularly in facilitating transaction recording, improving cash flow transparency, and providing accurate transaction evidence. However, its role has not been fully optimized due to several challenges, including low financial and digital literacy, inconsistent separation of personal and business finances, and technical constraints such as internet instability and fund disbursement delays. Therefore, digital payments have strong potential as a tool to enhance MSME financial accountability, but require adequate literacy and infrastructure support.